English Teaching in the Time of Crisis: A Case in Indonesia - Amanda Pradhani Yanwar; Edi Suwandi (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
This study aimed to investigate the use of Information and Communications Technology (ICT) in the teaching and learning process during the COVID-19 pandemic, the most online learning media used, and advantages and disadvantages of using ICT. This was quantitative qualitative research. The participants of this study were 110 English lecturers at universities in Indonesia. The techniques for collecting the data in this study were questionnaire, interview, and document analysis. In analyzing the data, the researchers used SPSS and Flow Model. There were three stages in the Flow Model, namely data reduction, data display, and conclusion drawing/verification. Based on the analysis of the data, it can be concluded that the English lecturers used several online learning media during English teaching and learning process. There were some advantages and disadvantages of using ICT during the teaching and learning process. It is recommended for English lecturers to use various online learning media so that the students will be enjoyable and get engaged in the learning process. English lecturers should also consider advantages and disadvantages during the use of ICT. For other researchers who want to conduct similar research, the result of this study can be an additional reference.